Phonological Processes of English Loanwords From French: A Transformational Generative Phonology Approach - Rizka Ayu Prihandani; Agus Subiyanto (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
English lexicon has borrowed from 84 languages with French as the most important donor (Bielenia-Grajewska, 2009). English borrowed a great number of lexicon from French in Norman Conquest period. French which had status as high language in a diglosia situation influenced English in superstate borrowing. The main reason for borrowing is to provide words from the source language variety when there is no suitable existing words in the target language (Rao, 2018). This paper aims at describing the phonological process in the English loanwords from French. The data were collected from two online dictionaries; Larousse Francais-Anglais Dictionary and Oxford Living Dictionary. The data are English loanwords from French enlisted under categories A and B in the dictionaries. The method used to analyze the data was distributional method. The results show that Assimilation occurs in 29 loanwords or 6.6% of the total process which makes Assimilation process the least in number of the total process. Neutralization covers 7.8% with 34 loanwords. Syllable Structure is undergone by 63 loanwords or 14.3% of the total process. Strengthening occurs in 117 loanwords or 26.7% of the total process. Weakening covers 43.6% of the total process with 191 loanwords. Therefore, Weakening is the phonological process most found in the study.